2018
DOI: 10.1242/jeb.177469
|View full text |Cite
|
Sign up to set email alerts
|

High activity before breeding improves reproductive performance by enhancing mitochondrial function and biogenesis

Abstract: Understanding of physiological responses of organisms is typically based on data collected during an isolated event. Although many fundamental insights have been gained from these studies, evaluating the response to a single event ignores the fact that each individual has experienced a unique set of events throughout its life that may have altered its physiology. The idea that prior experiences can influence subsequent performance is known as a carry-over effect. Carry-over effects may explain much of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Notably, production of ATP and generation of reactive oxygen species (ROS) have been shown to vary with mitochondrial genotype (Ellison & Burton, , ; Estes et al ., ; Hicks, Denver & Estes, ; Barreto & Burton, ; Barreto, Pereira & Burton, ; Latorre‐Pellicer et al ., ). In tractable systems, detailed examination of respiration profiles from isolated mitochondria could also reveal the mechanistic basis for lower fitness in compromised individuals (Chung, Bryant & Schulte, ; Mowry et al ., ; Zhang et al ., ). While rarely adopted, whole‐organism measurements of basal and maximal metabolic rates may also be useful for assessing the fitness consequences of mitonuclear interactions (Sunnucks et al ., ).…”
Section: Emerging Themes In Studies Of Mitonuclear Coadaptationmentioning
confidence: 97%
“…Notably, production of ATP and generation of reactive oxygen species (ROS) have been shown to vary with mitochondrial genotype (Ellison & Burton, , ; Estes et al ., ; Hicks, Denver & Estes, ; Barreto & Burton, ; Barreto, Pereira & Burton, ; Latorre‐Pellicer et al ., ). In tractable systems, detailed examination of respiration profiles from isolated mitochondria could also reveal the mechanistic basis for lower fitness in compromised individuals (Chung, Bryant & Schulte, ; Mowry et al ., ; Zhang et al ., ). While rarely adopted, whole‐organism measurements of basal and maximal metabolic rates may also be useful for assessing the fitness consequences of mitonuclear interactions (Sunnucks et al ., ).…”
Section: Emerging Themes In Studies Of Mitonuclear Coadaptationmentioning
confidence: 97%
“…Shephard et al (2018) recently characterized the effect of ɣ-radiation on reproductive performance in the cricket Acheta domesticus. Work by Zhang et al (2018) indicated that female mice that ran on a wheel before breeding produced more pups that were heavier at weaning than females that did not have a wheel. While longevity was not reported, they also found an increase in average egg size.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exogenous, environmental stressors, endogenous stressors have also been found to benefit organismal performance. Work by Zhang et al (2018) indicated that female mice that ran on a wheel before breeding produced more pups that were heavier at weaning than females that did not have a wheel.…”
Section: Discussionmentioning
confidence: 99%
“…oxidative phosphorylation) and exogenous (e.g. radiation) factors and inevitably impact the stability and performance of mitochondria (Zhang et al ., ) and, therefore, whole‐animal performance (Zhang et al ., ; Heine et al ., ).…”
Section: Oxidative Stress and Mitochondrial Morphologymentioning
confidence: 99%